Propuesta de recuperación de la laguna a partir de estrategias medioambientales: humedales urbanos, caso de estudio: polígono z30, Riobamba - Ecuador - Sánchez Buenaño, Alexis Ricardo (2025)
The lagoon in Polígono Z30 of Riobamba, Ecuador, is an important urban ecosystem that provides various ecosystem services and is vital for the quality of life of the local community. However, the lagoon has suffered significant environmental degradation due to factors such as pollution, erosion, sedimentation and water extraction, which has affected the health of the ecosystem and the services it provides, as well as the quality of life of the local community. Given this problem, the proposal to recover the lagoon through the implementation of environmental strategies, specifically the creation of urban wetlands, is presented as a viable and sustainable alternative to restore the health of the ecosystem and at the same time improve the quality of life of its people. around. This proposal for the recovery of the lagoon will be addressed within the framework of an investigation that will focus on the case study of the Z30 Polygon of Riobamba-Ecuador. Where, the design factors that have contributed to the environmental degradation of the lagoon will be analyzed, the effectiveness of the creation of urban wetlands as an environmental strategy for its recovery will be evaluated, without leaving aside the participation of the local community.